Caught in the Act of Quenching? – A Population of Post-Starburst Ultra-Diffuse Galaxies - Sandoval Ascencio, Loraine; Cooper, M. C.; Zaritsky, Dennis; Donnerstein, Richard; Khim, Donghyeon J.; Baxter, Devontae C. (The open journal of astrophysics, 2025)
We report the discovery of post-starburst ultra-diffuse galaxies (UDGs), identified through spectroscopic analysis with KCWI at the Keck II Telescope. Our analysis is based on a sample of 44 candidate UDGs selected from the Systematically Measuring Ultra-Diffuse Galaxies (SMUDGes) program. Our measured spectroscopic redshifts reveal ∼ 85 % of the entire KCWI sample exhibit large physical sizes () and low surface brightnesses ( 24 ≲ μ 0 , g ≲ 25 mag arcsec -2 ) which categorize them as UDGs. We find 20 % of the confirmed UDG population contain post-starburst (or K+A) features, characterized by minimal to no emission in H β indicative of quenched star formation and a predominant presence of spectral A-type stars. In surveying the local environments of the post-starburst UDGs, we find that nearly half are isolated systems, which is unusual given that isolated UDGs are most commonly found to be star-forming. Two of these systems reside away from potential nearby massive hosts ( M ⋆ > 10 10 M ⊙ ), indicating the absence of environmental influence. These post-starburst UDGs may represent systems experiencing star formation feedback such that a recent burst may lead to (at least temporary) quenching. Overall, our results highlight the potentially diverse quenching pathways of UDGs in the local Universe.